TURKISH CULTURE INFORMATION IN OMER SEYFETTIN'S POETRY - Rabia GÖKCEN KAYABAŞI (Fırat University, 2019)
Cultural elements have an important place in the life of every society on earth. Literary figures, who can guide the collective way of life and address the future generations, are trying to establish a connection between their works and their society by placing them in their works in the cultural elements of the societies they belong to. Ömer Seyfettin, one of the most important names in Turkish literature, has produced many literary works in different genres throughout his life. Ömer Seyfettin criticizes people who have lost their identities in their works and struggles for the society in chaos to return to self. For this reason, it gives a wide place to the elements of Turkish culture in literary works. When the works of Ömer Seyfettin are examined, it is seen that he has comprehensive knowledge of Turkish culture. He uses many elements of Turkish mythology successfully in his works. At this point, the public finds something in himself in his works, and therefore his works are easily understood by the public. Understanding by the public has brought along the spread of his works among the people. In his poems which he started to write since his studenthood, the reflection of the influence of the nationalism movement that emerged during the disintegration period of the Ottoman State, the reflection of Turkism and Turanism is seen. However, whichever mentality is involved, cultural elements are included as coded information in Seyfettin poems, and they also construct the content and philosophy of their work. In this study all the printed poems of Ömer Seyfettin were examined and the elements belonging to the Turkish culture within their poems were determined and tried to solve the coded information that they conveyed their thoughts in their poems.